Contact and Non-Contact Dual-Piezoelectric Energy Harvesting System Driven by Cantilever Vibration - Laihu Peng; Yubao Qi; Jianting Liu; Yuan Sun; Hongfei Zu; Xin Ru (IEEE Access, 2022)
In this study, a dual-piezoelectric energy harvesting system with contact and non-contact characteristics was driven by a cantilever beam. The harvester performance of the multipoint energy harvesting system driven by cantilever-beam vibration was designed, detailed analysis and optimization strategies were developed, and its application in the security field was successfully demonstrated. Herein, we provide theoretical guidance for the design of the dual-piezoelectric energy harvesting. We designed and fabricated a prototype of the dual-piezoelectric energy harvesting. A test system was designed and constructed. The relationships among the distance and frequency of the two piezoelectric acquisition mechanisms and the open-circuit voltage were investigated. Additionally, the effects of different loads on the output power were examined. The peak power reached 10.12 mW under a gravitational acceleration of 1g. The analysis indicated that the dual-piezoelectric energy harvest device has a higher energy harvest efficiency than the single-piezoelectric energy harvest device. Owing to the multipoint harvest strategy, even if a generator suddenly deteriorates or fails, the entire system can maintain a certain power output, which is more commercially feasible. The results of this study indicate that the output of the piezoelectric energy harvesting is stable and reliable and that the output energy satisfies the requirements for a safety warning device.